Քաղաքական ընդդիմության հարցի շուրջ - Ալեքսանդր Սարգսյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается сущность политической оппозиции, в частности, определение феномена в широком и узком смыслах и его институционализация. Автор проводит сравнительный анализ понятий «политическая оппозиция» и «оппозиционность». This article considers the nature of political opposition; especially the concise and expanded definitions of the concept and as well as its institutionalization. The author makes a comparative analysis of the "political opposition" and "opposition" concepts.
Keywords: Political Science